Generating Nested XML Documents with Dtd from Relational Views - Ahmed, Mohammed Nasser (2008)
Converting relational database into XML is increasing daily for publishing and exchanging data on the web. Most of the current approaches and tools for generating XML documents from relational database generate flat XML documents that contain data redundancy which leads to produce a massive data on the web. Other approaches assume that the relational database for generating nested XML documents is normalized. In addition, these approaches have problem that lies in the difficult of how to specify the parent elements from the children elements in the nested XML document. Moreover, most of the current approaches and tools do not generate nested XML documents automatically. They require the user to specify the constraints and the schema of the target document. This research proposes an approach to automatically generate nested XML documents from flat relational database views that are unnormalized. The research aims to reduce data redundancy and storage sizes for the generated XML documents. The proposed approach consists of three steps. The first step is converting flat relational view into nested relational view. The second is generating DTD from the nested relational view. The third is generating nested XML document from the nested relational view. The proposed approach is evaluated and compared to other approaches such as NeT, CoT, and Cost-Based and tools such as Allora, Altova, and DbToXml with respect to two measurements: data redundancy and storage size of the document. The first measurement includes several parameters that are number of data values, elements, attributes, and tags. Based on the results of comparing the proposed approach to several other approaches and tools, the proposed approach is more efficient for reducing data redundancy and storage size of XML documents. It can reduce data redundancy and storage size by approximately 50% and 55%, respectively.